2006
DOI: 10.1159/000091966
|View full text |Cite
|
Sign up to set email alerts
|

The Inverse Association of Elevated Serum Bilirubin Levels with Subclinical Carotid Atherosclerosis

Abstract: Background: Serum bilirubin is negatively associated with the development of coronary heart disease. In the present study, we have focused on the analysis of intima-media thickness (IMT) of the common carotid artery in hyper- and normobilirubinemic subjects. Methods: The study was performed on 111 men without manifested atherosclerosis. In all subjects, complete biochemical tests were determined along with the examination of IMT by carotid ultrasound. Results: The mean IMT in hyperbilirubinemic subjects as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 26 publications
7
80
0
Order By: Relevance
“…As a result, in this large representative population of males (N = 3408), we found an independent association between increasing concentration of serum total bilirubin and decreasing CAC score, a predictor for CHD risk. 12,13 Our findings were in line with those of previous reports concerning the inverse relation between bilirubin and prevalence of carotid plaque, 23 carotid IMT, 9,11 and PAD. 10 However, a recent study has reported that CAC score is a better predictor of subsequent CHD events than carotid IMT.…”
Section: Discussionsupporting
confidence: 93%
“…As a result, in this large representative population of males (N = 3408), we found an independent association between increasing concentration of serum total bilirubin and decreasing CAC score, a predictor for CHD risk. 12,13 Our findings were in line with those of previous reports concerning the inverse relation between bilirubin and prevalence of carotid plaque, 23 carotid IMT, 9,11 and PAD. 10 However, a recent study has reported that CAC score is a better predictor of subsequent CHD events than carotid IMT.…”
Section: Discussionsupporting
confidence: 93%
“…Our study therefore for the first time extends these findings to amputation events. This inverse association is further supported by studies showing a similar relationship between bilirubin levels and CHD, ischaemic stroke, and surrogate markers of atherosclerosis including endothelial dysfunction and carotid intima-media thickness [12,14,[29][30][31][32][33][34][35][36][37][38][39][40][41][42]. A number of prospective studies found a Uor reversed J-shaped relationship rather than an inverse relationship between bilirubin levels and CHD [4,5,27,28,30,33,34,37].…”
Section: Discussionmentioning
confidence: 78%
“…7,8 On the other hand, the question of a protective effect of Crigler -Najjar causing alleles at the heterozygote state against oxidative damages such as heart coronary diseases is not clear. Vitek et al 21 pointed that patients with mild increase of serum bilirubin could be protected against heart disease. But on the other hand, Bosma et al 22 and Gajdos et al 23 in two different studies did not find any correlation between mutations in UGT1A1 gene promoter and protection against heart disease.…”
Section: Discussionmentioning
confidence: 99%